Transaction Costs, Uncertainty and Generally Inactive Futures Markets - Shefrin, H. M. (Review of Economic Studies, 1981)
Journal Article Transaction Costs, Uncertainty and Generally Inactive Futures Markets Get access H. M. Shefrin H. M. Shefrin University of Santa Clara Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 48, Issue 1, January 1981, Pages 131–137, https://doi.org/10.2307/2297125 Published: 01 January 1981 Article history Received: 01 October 1978 Accepted: 01 April 1980 Published: 01 January 1981